A Rare Compound Heterozygous Mutation of TRPM6 Gene in Hereditary Hypomagnesemia with Secondary Hypocalcemia: A Cause of Refractory Seizures in an Infant - Chandreyee Bhattacharya; Rajiv Sinha; Subrata Dey; Kaushik Maulik (Wolters Kluwer Medknow Publications, 2024)
Background: Hypomagnesemia is an important cause of refractory hypocalcemic seizures. Among the causes of hypomagnesemia, genetic defects are rare. Clinical Description: A 20-month-old boy presented with a history of repeated hypocalcemic convulsions since 1 month of age. Besides seizures, the infant was thriving well and otherwise asymptomatic. Management and Outcome: On investigation, he had low serum calcium, normal vitamin D, low parathormone, and very low serum magnesium (0.5 mg/dl) levels, with normal sodium, potassium levels, and renal functions. The child was initiated on parenteral magnesium supplementation and subsequently discharged on high-dose oral magnesium supplementation. As further investigations ruled out common causes of hypomagnesemia, clinical exome sequencing was done, which revealed a compound heterozygous state with two variants in the TRPM6 gene NM_017662.5, one being a missense variant (chr9: c.5614T>C, [p.Trp1872Arg]/Heterozygous) and the other being a frameshift deletion (chr9: c.1939_1946delGCAATGGC, [p.Ala647Profs*2]/Heterozygous). The child maintained normal serum magnesium levels at follow-up and was seizure-free. Conclusion: Hereditary hypomagnesemia with secondary hypocalcemia is a rare cause of refractory seizures with onset since early infancy. Here, a compound heterozygous variant of the TRPM6 gene was identified as the cause of this condition.